Use of Table of Specification in Construction of Teacher-Made Achievement Test in Mathematics in the Primary and Secondary Schools - Osebhohiemen, Ehiagwina (The Melting Pot, 2019)
A sound primary and secondary education is fundamental in our educational system. Therefore, the use of table of specifications in the construction of teacher- made achievement test should not be overlooked in order to attain a sound primary and secondary education. The preparation of teacher made achievement test has been relegated to the background. When teacher made achievement test were introduced, results were good and easily understood. However because of lack of proper training on its use, it was abandoned. Hence false result and assessment were obtained, consequently resulting to students’ poor performance in the subject (Mathematics). Teachers are no longer prepared to test students and for most schools, teachers and administrators are still relatively blank as far as skills in test construction and interpretation are concerned. Therefore, this paper examined the possibility of achieving adequate assessment of pupils/students through the use of table of specification during the preparation of teacher-made achievement test in Mathematics in the primary school and secondary school levels. The importance of table of specifications and the inherent dangers of not using it were highlighted and recommendations to ameliorate the situation were proffered.